Corporate social responsibility practices and sustainable development. A systematic review from 2012 to 2022 (LACCEI, 2024)
Currently, citizens demand great changes focused on building a balanced and sustainable society for current and future generations, corporate social responsibility is shown as a tool to contribute to said development. This research seeks to identify the current perspectives of corporate social responsibility and its impact on sustainable development. For this, an investigation was developed using the systematic review methodology, analyzing review articles from the Ebsco, Scopus, ProQuest, Scielo, Redalyc and Dialnet databases, applying a search strategy that yielded 12,339 combined articles, which went through eligibility criteria for both inclusion (published articles, Latin American context, development of topic or subtopics) and exclusion (published before 2012, external context, incomplete information) obtaining, after removing duplicates, 65 articles for full review. The information was analyzed according to the CSR application perspective, and according to the type of CSR practice proposed. It is concluded that the vast majority of authors (62%) state that the prospects for the application of corporate social responsibility practices have an impact on sustainable development, placing particular emphasis on a characteristic of sustainable development according to the context or specific approach. of the place of operations or scope of the company. In addition, it constitutes a need for application, beyond the regulatory requirements, but as part of a business conscience.